Teacher Training from the perspective of Integral and Inclusive Education: practical experiences from different institutions - Silva e Souza, Maewa Martina Gomes da [UNESP]; Vieira, Camila Mugnai [UNESP]; Monteiro, Tamires Alves (Univ Federal Norte Tocantins-ufnt, 2024)
One of the principles of integral education is the perspective of inclusive education, which values differences and understands that it is in diversity that a truly democratic, fair and supportive space is built. From the National Policy on Special Education from the Perspective of Inclusive Education, it is understood that it is urgent to recognize and eliminate barriers to guarantee space for everyone. Therefore, this text aims to discuss the training experiences of teachers from the perspective of integral and inclusive education in private and public Higher Education institutions, focusing on the processes of two-degree courses (one in Pedagogy and the other in Languages) and a Teacher Development Center for Higher Education in the health sector. To this end, it is based on Joseph Puig's proposal of three curricular paths for education in values: interpersonal, which focuses on relationships between members of the school community; the curricular, which explores how these themes are addressed in training content; and institutional, which focuses on inclusive strategies and everyone's participation. When analyzing the training experiences of teachers, it is considered how the three curricular paths are implemented to promote the integral development of educators, respecting and ensuring inclusion in all their pedagogical practices.
Keywords: integral education; inclusive education; teacher training